The role of professional ethics in relation to organizational culture of primary school teachers in Mamsani city - Karami, Parvin; Rostami, Soheila (International Journal of Business Management and Entrepreneurship, 2023)
The current research aims to mediate the role of professional ethics in relation to organizational culture and organizational growth of primary school teachers in Mamsani city. This research is in terms of practical purpose, in terms of the type of research method, descriptive information and correlational studies, which data collection was done in the field through a questionnaire. The statistical population is all primary school teachers of Mamsani city. The data collection tool in this research included a standard questionnaire. Statistical operations were performed using spss and amos software. A strong organizational culture can be effective in better performance and greater adaptation of employees to the educational environment and cause the growth and prosperity of educational organizations and their development. The results of this study showed that There is a significant relationship between professional ethics on the organizational culture of primary school teachers in Mamsani city (P=0.001.05 and r=0.598), professional ethics variable with a value of 0.61 on the organizational culture of primary school teachers in the city Memsani has a direct effect.